(untitled) (Dhaka University Journal of Biological Sciences, 2024)
Violacein is a naturally-occurring bacterial secondary metabolite which is known to demonstrate a wide range of biological properties including antibacterial, antifungal, antiviral as well as anticancer and antitumor activities. Bacteria belonging to the genus Chromobacterium are the most studied microorganisms for violacein production. In this study, indigenous violacein-producing Chromobacterium violaceum was isolated from water and sediment samples of Bijaypur white clay hill lake, Netrokona, Bangladesh, and identified by biochemical and molecular characterization. After confirming the presence of the vioB gene in a polymerase chain reaction, crude violacein was purified from C. violaceum CV1 by ethanol extraction followed by filtration through 0.22 µm syringe filters. The partially-purified pigment exhibited significant antibacterial activity against three Gram-positive pathogens; Staphylococcus aureus, Streptococcus sp, and Listeria monocytogenes, with the later demonstrating the highest sensitivity. The bactericidal activity was more pronounced when combined with an antibiotic, thereby producing a drug-metabolite synergistic antibacterial activity. Dhaka Univ. J. Biol. Sci. 33(1): 109-119, 2024 (January)